Factors associated with reoperation in hypospadias surgery — A nationwide, population-based study - Yu-Chuan Lu; Wei-Yi Huang; Yu-Fen Chen; Hong-Chiang Chang; Yuan-Hung Pong; Tsung-Hsien Shih; Kuo-How Huang (Asian Journal of Surgery, 2017)
Background/Objective: To analyze the preoperative factors associated with the need for secondary surgery following primary urethroplasty. Methods: This study utilized a subset of the National Health Insurance Research Database, which includes the data on all paid medical benefit claims from 1997 to 2007, for 1 million beneficiaries in 2005. We analyzed the claims data for all patients with hypospadias who had undergone primary urethroplasty. The characteristics of the patients, surgeons, and hospitals associated with surgical outcomes were analyzed to investigate possible associations with the need for secondary surgery. Results: Among 52,705 live male newborn babies, 218 were diagnosed with hypospadias, of whom 89 received repair surgery. A total of 75 (84.3%) male newborn babies received single hypospadias surgery, and 14 (15.7%) underwent more than two surgical procedures. Univariate analysis demonstrated that the type of hypospadias and the surgeon caseload volume were significantly associated with the need for additional hypospadias surgery (p = 0.02 and p = 0.03, respectively). In multivariate analysis, the type of hypospadias (distal vs. proximal, odds ratio, 0.25; p = 0.03) and the surgeon caseload volume (high vs. low, odds ratio, 0.04; p = 0.05) were significantly correlated with secondary operation. Conclusion: The type of hypospadias and the surgeon caseload volume were significantly associated with the need for secondary hypospadias surgery. The findings of this study provide important information on the outcomes of hypospadias repair for parents and specialists.